ANALYSIS OF DRUG-RELATED PROBLEMS (DRPs) AND THERAPEUTIC RATIONALITY IN TWO DIFFERENT CLINICAL CASES: ABDOMINAL COLIC IN ADOLESCENTS AND VERTIGO IN ADULT PATIENTS IN HOSPITALS - Rangki Astiani; Piter Piter; Ria Anggraeni; Maria Sheila Setya Ningtyas; Farisa Luthfiana; Valerie Kezia; Mardianti Borean (Universitas 17 Agustus 1945 Jakarta, 2026)
ABSTRACTDrug-Related Problems (DRPs) are common issues in healthcare services and can affect the success of patient therapy. Abdominal colic is a disorder of normal intestinal flow throughout the intestinal tract caused by infection in the abdominal organs, while vertigo is a sensation that the patient is moving or spinning, or that objects around the patient are moving or spinning, usually accompanied by nausea caused by an imbalance in the three types of AKT receptors (Body Balance System) due to excessive stimulation. The purpose of this report is to review the rationality of therapy in two different clinical cases. A retrospective case study was conducted by analyzing patient medical records, DRPS analysis, physical examination, laboratory tests, pharmacological therapy, and clinical response. The first patient was given analgesic, anti-inflammatory, antibiotic, and fluid therapy for hydration. The second patient was given first-line vertigo therapy, antihypertensive drugs, and gastric protection. Therapy adjustments were made according to patient response and laboratory parameters. Clinical pharmacy monitoring ensured pain control and monitored side effects and drug interactions.